Multidimension Of Family Financial Management Effectiveness - Zuhri, Ach. (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study is to provide a literature review on various aspects of family financial management and to determine the most effective aspects of financial management in managing family finances. The method used in this study is to use the method of literature study / study of the literature. This research examines 50 scientific articles from reputable international journals. Financial management from the aspects of financial knowledge, financial culture, financial need, financial literacy, and financial barriers that have been studied by previous researchers is quite complex. However, what needs to be prioritized for families or households to learn is financial management from the aspects of financial knowledge and financial culture, because these two aspects play the most role in the effectiveness of family financial management. Financial obstacles are indeed a negative aspect for financial management, because we are required to be more able to adjust and meet financial needs that are not appropriate (at a minimum).